Effect of nitrogen pressure on the structural and mechanical properties of V-Mo-N coatings deposited by cathodic arc evaporation - Kuprin, A.S.; Reshetnyak, E.N.; Gilewicz, A.; Warcholinski, B.; Vasilenko, R.L.; Rostova, H.Yu.; Klimenko, I.O.; Tolmachova, G.N.; Ilchenko, A.V. (Вопросы атомной науки и техники, 2022)
The coatings of the V-Mo-N system were deposited by the cathodic arc evaporation method from the unfiltered plasma of two V and Mo cathodes. Electron microscopy, energy dispersive analysis, X-ray diffractometry, nanoindentation, and adhesion testing have been used to study the effect of nitrogen pressure during deposition on surface morphology, composition, structure, and mechanical properties of coatings. It was found that at a nitrogen pressure of 1 Pa the V₂₉Mo₂₁N₅₀ coating formed with a predominantly cubic c-(V,Mo)N structure and an insignificant fraction of hexagonal h-(Mo,V)N. With an increase in the pressure of the reaction gas to 2…3 Pa, a gradual increase in the concentration of nitrogen up to 54 at.% and molybdenum up to 26 at.% is observed, which leads to a slight increase in the hexagonal phase concentration. All coatings are characterized by a fairly good surface quality, high hardness of 30…32 GPa and adhesion to the steel substrate. The c-(V,Mo)N coating has better resistance to crack propagation, correlates with a maximum H³/E² – 0.18, and combines high hardness and ductility. Покриття системи V-Mo-N осаджували вакуумно-дуговим методом з нефільтрованої плазми двох катодів з V та Mo. Методами електронної мікроскопії, енергодисперсійного аналізу, рентгенівської дифрактометрії, наноіндентування та адгезійного тестування досліджено вплив зміни тиску азоту при осадженні на морфологію поверхні, склад, структуру та механічні властивості покриттів. З’ясовано, що при тиску азоту 1 Па формується покриття V₂₉Mo₂₁N₅₀ з переважно кубічною структурою c-(V,Mo)N і незначною часткою гексагонального h-(Mo,V)N. Збільшення тиску реакційного газу до 2…3 Па викликає поступове зростання концентрації азоту до 54 ат.% і молібдену до 26 ат.%, що призводить до невеликого збільшення вмісту гексагональної фази. Усі покриття характеризуються достатньо гарною якістю поверхні, високими показниками твердості (30…32 ГПа) та адгезії до сталевої підкладки. Покриття c-(V,Mo)N демонструють при навантаженні кращу стійкість до поширення тріщин, що корелює з максимальним значенням параметрa H³/E² – 0,18, і також поєднання високої твердості та пластичності.